2013
DOI: 10.1186/1471-230x-13-86
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric treatment considerations with direct acting antivirals in hepatitis C

Abstract: BackgroundDespite recent advances in hepatitis C (HCV) treatment, specifically the addition of direct acting antivirals (DAAs), pegylated interferon-alpha remains the backbone of HCV therapy. Therefore, the impact of DAAs on the management of co-morbid psychiatric illness and neuropsychiatric sequalae remains an ongoing concern during HCV therapy. This paper provides a review of the neuropsychiatric adverse effects of DAAs and drug-drug interactions (DDIs) between DAAs and psychiatric medications.MethodsWe con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 75 publications
(79 reference statements)
0
22
0
Order By: Relevance
“…However, a contraindication of this regimen is depression since treatment with pegylated IFNα can induce neuropsychiatric side events, such as depression, in 25–40% of all patients undergoing IFNα therapy for HCV 5 7–12. Furthermore, according to Sockalingam et al , ‘HCV-infected patients with pre-existing psychiatric disorders may have an exacerbation of a secondary psychopathology related to IFNα’,13 and ‘the onset of suicidal ideation and suicide during HCV therapy in general population coincide with the onset of IFNα-induced neuropsychiatric symptoms (IFNα-D)’ 14 15. Nevertheless, no data regarding the prevalence of neuropsychiatric symptoms in patients with psychiatric risk are available.…”
Section: Introductionmentioning
confidence: 99%
“…However, a contraindication of this regimen is depression since treatment with pegylated IFNα can induce neuropsychiatric side events, such as depression, in 25–40% of all patients undergoing IFNα therapy for HCV 5 7–12. Furthermore, according to Sockalingam et al , ‘HCV-infected patients with pre-existing psychiatric disorders may have an exacerbation of a secondary psychopathology related to IFNα’,13 and ‘the onset of suicidal ideation and suicide during HCV therapy in general population coincide with the onset of IFNα-induced neuropsychiatric symptoms (IFNα-D)’ 14 15. Nevertheless, no data regarding the prevalence of neuropsychiatric symptoms in patients with psychiatric risk are available.…”
Section: Introductionmentioning
confidence: 99%
“…43 Current clinical trials showed that other recently approved or approval awaiting -HCV NS5A inhibitors (daclatasvir, ledipasvir) or HCV NS5B polymerase inhibitors (sofosbuvir, deleobuvir) also lack adverse effects that could significantly deteriorate patients mental condition. 43,44 However, DAAs are highly active antivirals, they have a low barrier to resistance. Thus, a combined treatment with PEG-IFN and RBV is being recommended, making the overall efficacy still dependent on individual IFN sensitivity and adverse effects tolerance.…”
Section: Ifn and Daas Therapymentioning
confidence: 99%
“…43 However, DAAs do not pose neuropsychiatric risk directly; they may interact with psychotropic agents through P450 cytochrome and p-glycoprotein. 43,44 The contraindicated drugs list includes: midazolam, carbamazepine, pimozide and hypericum perforatum. Interactions between PIs and SSRIs or SNRIs may exacerbate adverse effect or decrease blood plasma concentrations.…”
Section: Ifn and Daas Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the recent FDA approval of two new oral medications, bocepravir and telapravir termed direct-acting antiviral medications, have been shown to enhance treatment responses of patients with genotype I infection, as well as, those who have previously failed interferon-based treatment [62]. Both methadone and buprenorphine have been shown not to have significant drug interactions with these hepatitis C medications and so can be co-administered [63], although the presence of adverse events should continue to be monitored clinically since experience with these combinations in practice is quite limited to date. The approach to treatment of hepatitis C may soon change to the use of oral medications rather than a combination of interferon, an injected therapeutic and oral medications.…”
Section: Treatment Of Chronic Hepatitis C Infection and Methadone Or mentioning
confidence: 99%